2003
DOI: 10.1029/2002jd003227
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and transport of sulfur dioxide over the Yellow Sea during TRACE‐P

Abstract: [1] Fast time resolution (>1 Hz) sulfur dioxide (SO 2 ) measurements were obtained using an atmospheric pressure ionization mass spectrometer with isotopically labeled internal standard on the NASA Wallops P-3B during the NASA Transport and Chemical Evolution Over the Pacific (TRACE-P) field experiment. The high time resolution for SO 2 allowed a view into the dynamics of SO 2 transport, including the effects of clouds. Two missions along 124.5°E from the vicinity of Taiwan to the northern Yellow Sea near the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…New to the GTE program were measurements of oxygenated organics aboard the DC‐8 by Gas Chromatography and Mass Spectroscopy (GC‐MS) [ Apel et al , 2003], measurements of HCHO aboard the DC‐8 by Tunable Diode Laser Spectroscopy (TDLS) [ Fried et al , 2003], measurements of peroxy radicals aboard the P‐3B by Chemical Ionization Mass Spectroscopy (PerCIMS) [ Cantrell et al , 2003], fast measurements of bulk aerosol composition aboard the P‐3B by the Particle‐Into‐Liquid Sampler (PILS) [ Ma et al , 2003], fast measurements of SO 2 by Atmospheric Pressure Ionization Mass Spectrometry (APIMS) [ Tu et al , 2003], and measurements of PAN by GC‐MS aboard the P‐3B (F. Flocke). New capabilities were also added to existing instruments, e.g., GC measurements of HCN and CH 3 CN [ Singh et al , 2003] and CIMS measurements of HNO 3 [ Zondlo et al , 2003].…”
Section: Designmentioning
confidence: 99%
“…New to the GTE program were measurements of oxygenated organics aboard the DC‐8 by Gas Chromatography and Mass Spectroscopy (GC‐MS) [ Apel et al , 2003], measurements of HCHO aboard the DC‐8 by Tunable Diode Laser Spectroscopy (TDLS) [ Fried et al , 2003], measurements of peroxy radicals aboard the P‐3B by Chemical Ionization Mass Spectroscopy (PerCIMS) [ Cantrell et al , 2003], fast measurements of bulk aerosol composition aboard the P‐3B by the Particle‐Into‐Liquid Sampler (PILS) [ Ma et al , 2003], fast measurements of SO 2 by Atmospheric Pressure Ionization Mass Spectrometry (APIMS) [ Tu et al , 2003], and measurements of PAN by GC‐MS aboard the P‐3B (F. Flocke). New capabilities were also added to existing instruments, e.g., GC measurements of HCN and CH 3 CN [ Singh et al , 2003] and CIMS measurements of HNO 3 [ Zondlo et al , 2003].…”
Section: Designmentioning
confidence: 99%
“…The size distribution of airborne particles over eastern coastal areas (W. , vertical ultrafine particles profiles over northern China coastal areas during dust storms (Wang et al, 2008a) and gaseous and particulate pollutants over Pearl River Delta (Wang et al, 2008b) have been studied. Other aircraft observations from the Transport and Chemical Evolution over the Pacific Experiment (TRACE-P; Tu et al, 2003) showed substantial concentrations of SO 2 over the Pacific downwind of China . Another Chinese-American joint project, EAST-AIRE (the East Asian Study of Tropospheric Aerosols: an International Regional Experiment; Li et al, 2007) investigated the vertical distribution of pollutants and dust over east Asia from eight flights under a variety of weather conditions in northeastern China centered over Shenyang, a large industrial city 650 km northeast of Beijing, shedding light on the mechanisms of long-range pol- lutant transport out of east Asia .…”
Section: Introductionmentioning
confidence: 99%
“…Their work indicated that the transport occurred in layers, which were bounded by thin turbulent layers, and would therefore maintain their integrity over significant distances. For the SO 2 transport, Tu et al [2003] reported the observations over the Yellow Sea during the TRACE‐P mission flights 13 and 14. These observations indicated that the SO 2 transport usually occurred in layers characterized by low turbulence and were often further constrained by temperature inversions.…”
Section: Resultsmentioning
confidence: 99%
“…Further study revealed that rain showers were encountered between 0040 and 0200 UTC and no rain showers along the flight track after 0200 UTC. Tu et al [2003] suggested that the STEM‐2K1 model usually overestimated the SO 2 concentrations when precipitation was encountered. The observations during flight 18 suggested that a large fraction of SO 2 had been removed by heterogeneous processing prior to 0040–0200 UTC.…”
Section: Resultsmentioning
confidence: 99%